Translation and linguistic validation of the Swedish recovering quality of life (ReQoL) – A brief research report - Granholm Valmari, Elin; Melander, Marianne; Hariz, Gun-Marie; Naesström, Matilda; Lindström, Maria (Frontiers in Psychiatry, 2023)
In research and among clinicians, the focus has shifted from mainly symptom reduction and increasing functionality to a more recovery-oriented focus. Although there are instruments measuring recovery, there has been a lack of instruments sensitive enough to measure the quality of life for people with severe mental health disorders. Therefore, this study aimed to obtain a Swedish version of the Recovering Quality of Life (ReQoL) questionnaire adhering to best practice guidelines using various steps of translation, linguistic validation, and cognitive debriefing. The cognitive debriefing was conducted with seven participants, and all felt the items in the questionnaire were relevant to their health, apprehensible, and easy to complete. However, some issues were raised regarding wording and the concepts behind certain items. All feedback was considered, and some items were revised in response to criticism after continuous discussions. A Swedish version of ReQoL now exists, and although there is a need for ReQoL in different clinical research settings in Sweden, further research is required to psychometrically test the construct validity as well as reliability of the Swedish version in Sweden.